Decouple design of leader-following consensus control for nonlinear multi-agent systems. Issue 1 (1st January 2020) - Han, Fei; He, Qianqian; Gao, Hongyu; Song, Jinbo; Li, Jiahui
Abstract : This paper addresses the H ∞ -consensus control problem for a class of discrete-time nonlinear multi-agent systems with missing measurements. First of all, the multi-agent systems under consideration are composed of N followers and a leader, where all agents are of nonlinear characteristics and all followers need to track the leader. Next, the measurements of all agents are not reliable, which could cause the occurrence of the missing measurements. In order to mitigate the computation burden stemming from the complicated couplings among the agents, the spectral decomposition and coordinate transformation are introduced to decouple the closed-loop systems into multiple independent subsystems. Then, a sufficient condition is established for the existence of the H ∞ -consensus controller ensuring that the closed-loop multi-agent system achieves the H ∞ -consensus performance by means of the Lyapunov stability theory. Besides, the controller parameters are obtained by solving some linear matrix inequalities. Finally, a simulation example is utilized to illustrate the effectiveness of the proposed control algorithm.